PRAKTIK KEAGAMAAN DIGITAL (DIGITAL RELIGION) PADA JEMAAT GEREJA KRISTEN KUDUS INDONESIA RUMAH DOA HOSANA (GKKI RDH) KOTA DENPASAR - Sitorus, Kristina; Tamim, Imron Hadi; Nugroho, Wahyu Budi (JURNAL ILMIAH SOSIOLOGI: SOROT, 2024)
This research focuses on the phenomenon of changing traditional religious practices into digital religious practices in the congregation of the Indonesian Holy Christian Church Hosana Prayer House (GKKI RDH), Denpasar City. This research aims to explain and analyze digital religious practices and the congregation's perceptions of the presence of technology in religious practices at the GKKI RDH church, Denpasar City. The method used in this research is a qualitative approach with a descriptive- explanatory type. The theory used as a scalpel to analyze this research is William F. Ogburn's theory of social change. The results of this research reveal that the implementation of digital religious practices began in 2020 when the Covid-19 virus attacked Indonesia. The reason behind why the GKKI RDH church implements digital religious practices is because the government issued regulations to carry out activities from home and away from crowds. Apart from that, the implementation of digital religious practices at the GKKI RDH church is also to ensure that the entire congregation continues to carry out their worship and also hopes that the congregation can start learning to operate digital technology that is currently developing. The presence of technology in religious practices makes it easier for congregations to carry out their religious practices so that digital religious practices can be said to be effective and efficient. Also, digital religious practices remain sacred, because true worship is a person's own person, not the form in which the worship is carried out. However, in fact, digital religious practices are not going well at the GKKI RDH church. This is because the congregation is still dominated by elderly parents, making it difficult for them to accept and learn new things. Apart from that, the level of congregational literacy regarding technological developments is still low, which makes the implementation of digital religious practices experience many obstacles as well as supporting economic factors.